Artificial Intelligence in Oral Medicine: A Review - Sameen R. J. (Medical Research and Its Applications Vol. 10, 2024)
Artificial Intelligence (AI) is increasingly becoming a transformative force in various fields, including oral medicine. A systematic review of AI applications in oral medicine reveals significant advancements and diverse applications that promise to enhance diagnostic accuracy, treatment planning, and patient management. This review synthesizes current research, highlighting the methodologies, outcomes, and potential future directions of AI in oral medicine.